SEXUAL HARASSMENT AT WORK PLACE: ARE YOU SAFE? - Naveed, Anila; Tharani, Ambreen; Alwani, Nasreen (Journal of Ayub Medical College Abbottabad, 2010)
In today's world women are increasingly participating in the realm of work force, yet they are facing many obstacles in their way. Sexual harassment is one of those obstacles. Sexual harassment at work place is prevalent in every society. It could happen to anyone but women are the targeted victims. Sexual harassment is considered as a traumatic event and the victim may end up in having physical and mental sufferings that hinders a person to work effectively. At an organisational level this may result in decrease work effectiveness, decreased work productivity, high absenteeism, high turnover, and low staff morale. Hence there is a need that, organisations and government should look seriously into this matter. Proper education and training programs should be developed to deal with these issues. The goal must be both to deal with sexual harassment incidents effectively and to prevent the occurrence of future incidents. Keywords: work place, harassment, training programs